Commissive Speech Act in Indonesian Presidential Debate - Husain, Abdulloh; Hamamah, Hamamah; Nurhayani, Ika (OKARA: Jurnal Bahasa dan Sastra, 2020)
A presidential debate is one of the campaign media which has a function to promote a presidential candidate to be a president. A linguistics theory of meaning was used to describe the utterances of the illocutionary act. This study was aimed to find a commissive speech act and its function in the first Indonesian presidential debate in 2019. The data source of this study was a video taken from Kompas TV channel on YouTube. The data of this study were utterances produced by the candidates. The data were collected by watching and note-taking techniques. As a result, 20 utterances belonged to the commissive speech act produced by Jokowi, Prabowo, and Sandi. However, there were no commissive speech act utterances produced by Ma'ruf. The conclusion is that the candidates mostly used promise act in producing utterances. The promise acts appear in the future tense, if clause condition sentence, and expression of InsyaAllah. Meanwhile, the function of producing utterances in this study is to show the candidates' capability to gain the consideration of society to vote one of them with a good sympathy.